2007
DOI: 10.1088/0031-9155/52/5/011
|View full text |Cite
|
Sign up to set email alerts
|

On the dosimetric behaviour of photon dose calculation algorithms in the presence of simple geometric heterogeneities: comparison with Monte Carlo calculations

Abstract: A comparative study was performed to reveal differences and relative figures of merit of seven different calculation algorithms for photon beams when applied to inhomogeneous media. The following algorithms were investigated: Varian Eclipse: the anisotropic analytical algorithm, and the pencil beam with modified Batho correction; Nucletron Helax-TMS: the collapsed cone and the pencil beam with equivalent path length correction; CMS XiO: the multigrid superposition and the fast Fourier transform convolution; Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
156
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(164 citation statements)
references
References 36 publications
5
156
1
2
Order By: Relevance
“…2 A number of studies have shown the limitation of photon dose calculation algorithms such as analytical anisotropic algorithm (AAA), collapsed cone convolution (CCC) algorithm, and pencil beam convolution (PBC) algorithm when complex geometry with inhomogeneity is involved along the photon beam path. [3][4][5][6][7][8][9][10][11][12] Both the AAA and CCC are based on the superposition/convolution method, which calculates the dose by superposition of dose kernels of primary and scatter components that are derived from the Monte Carlo (MC). The tissue inhomogeneity correction in superposition/convolution method such as in the AAA is done both in the beamlet direction and lateral directions.…”
Section: Introductionmentioning
confidence: 99%
“…2 A number of studies have shown the limitation of photon dose calculation algorithms such as analytical anisotropic algorithm (AAA), collapsed cone convolution (CCC) algorithm, and pencil beam convolution (PBC) algorithm when complex geometry with inhomogeneity is involved along the photon beam path. [3][4][5][6][7][8][9][10][11][12] Both the AAA and CCC are based on the superposition/convolution method, which calculates the dose by superposition of dose kernels of primary and scatter components that are derived from the Monte Carlo (MC). The tissue inhomogeneity correction in superposition/convolution method such as in the AAA is done both in the beamlet direction and lateral directions.…”
Section: Introductionmentioning
confidence: 99%
“…( 6 ) Another challenge comes from the dose calculation in a heterogeneous medium. ( 7 ) Currently, dose calculation algorithms with heterogeneity correction are not consistent among different treatment planning systems, ( 8 12 ) depending on how the changes in lateral electron transport are taken into account. ( 13 ) For this reason, dose calculations without heterogeneity correction were required in RTOG 0236, ( 14 ) which was a phase II trial of SBRT in the early stages of medically inoperable NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…One such dose calculation algorithm is the collapsed cone convolution algorithm implemented in the Pinnacle treatment planning system (Philips Healthcare, Andover, MA), which has demonstrated accurate dose calculations in the heterogeneous medium. ( 11 , 12 ) Using the Pinnacle treatment planning system (TPS), Xiao et al ( 15 ) have retrospectively analyzed treatment plans submitted to RTOG 0236 from multiple institutions. Significant dose differences were found when heterogeneity correction was applied.…”
Section: Introductionmentioning
confidence: 99%
“…The improved accuracy of the AAA in phantom situations and 3D conformal radiotherapy (3D-CRT) treatment plans compared to Eclipse's Pencil Beam Convolution (PBC) algorithm (the Eclipse implementation of the Single Pencil Beam algorithm of the same manufacturer's CadPlan TPS) has been reported by several authors [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%